Water Shortage in Jordan - Odeh, Omar (International Journal of Engineering and Management Sciences, 2019)
Water shortage in Jordan is considered to be one of the main challenges that face the country throughout the years. In this manuscript all aspects of this issue will be highlighted.  In this article, first, the water situation inputs, contests and outputs will be discussed. Secondly, there will be a detailed study about the ‘WADI AL-ARAB’ Project which is funded by the European Investment Bank and managed by the Yarmouk Water Company, its missions, assets and workflow. Finally, the Improvement of Energy Efficiency in the water sector, project aims, framework, and the major findings expected as a result of these analysis will be highlighted. This document presents the essential elements of a work that required a long time, an enormous effort and a hard work to collect all the data from several sources such as the Jordanian Ministry of Water and Irrigation (MWI), the Water Authority of Jordan (WAJ) and the European Commission (EU Official Website) and analyze them. Also, all the information listed about “WADI AL ARAB” Project was collected from multiple site visits.